2002
DOI: 10.1097/00002030-200203290-00003
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of DC-SIGN+CD40+ dendritic cells with reduced CD80 and CD86 expression in lymphoid tissue during acute HIV-1 infection

Abstract: In the early phase of HIV-1 infection, there was a migration of DC to LT comparable to that found in acute EBV infection. The infiltration of DC in LT in acute EBV infection was accompanied by upregulation of CD80 and CD86 expression, which did not occur in aHI. This co-stimulatory defect in aHI may have an impact on the development of HIV-1-specific T cell immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 33 publications
10
109
1
Order By: Relevance
“…A similar increase in the number of mature DC-SIGN ϩ DCs has been reported during acute Epstein-Barr virus infections. 34 However, no changes in DC-SIGN-and L-SIGN-expressing cells in the paracortical outer zone were observed as determined by double stainings (not shown), although the amount of L-SIGN ϩ sinus endothelial cells increased dramatically in enlarged lymph nodes (Figure 4C, right).…”
Section: Expression Of Dc-sign and L-sign In Immune Reactive Lymph Nodesmentioning
confidence: 83%
“…A similar increase in the number of mature DC-SIGN ϩ DCs has been reported during acute Epstein-Barr virus infections. 34 However, no changes in DC-SIGN-and L-SIGN-expressing cells in the paracortical outer zone were observed as determined by double stainings (not shown), although the amount of L-SIGN ϩ sinus endothelial cells increased dramatically in enlarged lymph nodes (Figure 4C, right).…”
Section: Expression Of Dc-sign and L-sign In Immune Reactive Lymph Nodesmentioning
confidence: 83%
“…Reduced numbers of circulating DCs have been reported in HIVinfected people, correlating with increased virus load (27)(28)(29)(30)(31), suggesting possible redistribution of DCs from the periphery to the lymphoid tissues. However, the number of interdigitating DCs is reduced in patients with AIDS (32). The expression of costimulatory molecules CD80 and CD86 on LN DCs during HIV infection might be insufficient for induction of adequate antiviral responses (32).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…However, the number of interdigitating DCs is reduced in patients with AIDS (32). The expression of costimulatory molecules CD80 and CD86 on LN DCs during HIV infection might be insufficient for induction of adequate antiviral responses (32). Macaque studies also demonstrated that DC maturation and frequency in LNs are affected during SIV infection (33,34).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…1). Indeed, it has been reported that some viral and bacterial proteins expressed inside cells directly interfere with T cell priming by modulating the expression of MHC or co-stimulatory molecules (57)(58)(59)(60). Consequently, dominant and subdominant epitopes are not efficiently presented to T cells, which means that T cells are not optimally activated or often tolerated in some cases.…”
Section: Extrinsic Factors Regulating T Cell Immunity In a Chronic Anmentioning
confidence: 99%